1998
DOI: 10.1177/096368979800700409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a New Immunosuppressive Agent, Fty720, on Survival of Islet Allografts

Abstract: A newly developed immunosuppressant, FTY720, has a unique mechanism that is quite different from those of conventional immunosuppressants, and is presumed to be mediated through decreases in the number of peripheral lymphocytes, especially helper T cells. This study was performed to ascertain whether this innovative drug could prolong islet allograft survival. The donors were inbred Lewis rats and the recipients were ACI rats rendered hyperglycemic with intravenous streptozotocin. In the study group, FTY720 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This drug reaches a maximum concentration at 8 or 9 h, and its metabolites are found in the urine and feces at ratios of 40-50 and 20-50%, respectively [3]. It has been reported that FTY720 exhibits beneficial effects on various kinds of organ transplantations in the rat system; skin, heart, liver, small bowel, and islet grafts [4][5][6][7]. Until now, the mechanism of immunosuppression by this drug has been supposed to be due to induction of apoptosis of the lymphocytes, because FTY720 induced chromatin condensation, formation of apoptotic bodies and DNA fragmentation in lymphocytes [8].…”
Section: Introductionmentioning
confidence: 99%
“…This drug reaches a maximum concentration at 8 or 9 h, and its metabolites are found in the urine and feces at ratios of 40-50 and 20-50%, respectively [3]. It has been reported that FTY720 exhibits beneficial effects on various kinds of organ transplantations in the rat system; skin, heart, liver, small bowel, and islet grafts [4][5][6][7]. Until now, the mechanism of immunosuppression by this drug has been supposed to be due to induction of apoptosis of the lymphocytes, because FTY720 induced chromatin condensation, formation of apoptotic bodies and DNA fragmentation in lymphocytes [8].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Upon oral administration, FTY720 prolongs survival of transplanted allografts without noticeable toxicity to the host, 1,[4][5][6][7][8][9] but the original product, ISP-1, causes severe digestive disorders, resulting in death of the animal. 2,3) Administration of a single dose of 10 mg W kg FTY720 to healthy rats reduces the number of peripheral lymphocytes, with a minimum by 3 h after the administration; recovery of the lymphocyte counts to pretreatment levels takes 2 weeks.…”
mentioning
confidence: 99%
“…The novel immunosuppressant, FTY720, 2-amino-2-(2-(4-octylphenyl) ethyl)-1,3-propanediol hydrochloride, was screened from synthesized analogs of ISP-1, which is an immunosuppressive metabolite of Isaria sinclairii (28 -31). The oral administration of FTY720 prolongs allograft survival in experimental organ transplantation without producing any noticeable side effects (31)(32)(33)(34)(35). The action mechanism of orally administered FTY720 to suppress graft rejection is regarded as a significant decrease in the number of blood lymphocytes, especially T cells (36).…”
mentioning
confidence: 99%